Development of an Individual Professional Development Plan Proposal That is Based on Continuing Professional Development Needs of Teachers - Bayram Özer; Taner Can; Volkan Duran (The European Educational Researcher, 2020)
The research was conducted to determine the needs of teachers for their continuous professional development and to create an individual professional development plan for this aim. For this purpose, descriptive survey model was used as a method. There are both qualitative and quantitative data in the research. The collection of research data was done in three stages. A survey was conducted in the first stage. At this stage, the population of the research consists of teachers from social networking networks facebook, instangram and whatsApp, which are included in the teacher groups of 529.412 individuals. The sample is composed of 507 teachers who voluntarily respond to the sharing in these groups. In the second phase of the study, focus group interviews were conducted with experts, teachers' professional development needs were determined, and solutions were reported. In the third phase of the research method, relevant literature regarding the teachers’ professional development activities in the world and how these activities were carried out were collected through literature review. As a result of the research, the data gathered by the methods mentioned in the study were combined and an individual professional development plan proposal was prepared. The importance of individual professional development is emphasized for the professional development of teachers.